Utilization of micro-debriefing in medical student simulation: An emergency department experience - Yuan Helen Zhang; Man Xin Lee; Fatimah Lateef (Proceedings of Singapore Healthcare)
Simulation-based education among novice learners emphasizes cost-effective debriefing and the purpose of this mix-method study is to evaluate the efficacy of micro-debriefing. Sixty-one medical students on emergency medicine core posting were recruited to complete the anonymous Debriefing Assessment for Simulation in Healthcare form together with a free-text questionnaire after their mandatory simulation session. Micro-debriefing instructors were rated well on all six elements (mean = 6.86–6.92). Thematic analysis of 95 free-text revealed key themes surrounding guided nature of micro-debrief, exemplary learning experiences and sufficient psychological safety. Micro-debriefing resulted in efficacious learning experience within a psychologically safe environment which substantiated its utility in the future of simulation-based medical education.